The Effect of Administering Humic Acid and Nasa POC Concentration on the Growth and Yield of Shallots (Allium Ascalonicum L.) - Sulistiyo Budi, Luluk; Ari Wibowo, Agus; Setyo Martono, Djoko (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This study aimed to examine the effect and interaction between the application of Humic Acid and the concentration of NASA liquid organic fertilizer (POC) on the growth and yield of shallots (Allium ascalonicum L.). This study was conducted from February to April 2025 in Sugihwaras Village, Saradan District, Madiun Regency using a factorial Randomized Block Design (RAK) with two factors: Humic Acid (A0 = 0 g/polybag, A1 = 2 g/polybag, A2 = 4 g/polybag) and NASA liquid organic fertilizer concentration (P1 = 2 ml/L, P2 = 5 ml/L, P3 = 8 ml/L). Each treatment combination was replicated three times, resulting in 27 plots with a total of 216 plants. The observed parameters included plant height, number of leaves, leaf area, number of tillers, number of bulbs, fresh bulb weight, dry bulb weight, and bulb diameter. Data were analyzed using ANOVA followed by a 5% DMRT test. The results of the study showed that there was an interaction between the treatment of Humic Acid administration and Nasa POC concentration on the parameters of plant height, number of leaves, number of tillers, number of tubers, wet weight of tubers, and dry weight of tubers, but there was no interaction on the parameters of leaf area and tuber diameter at the age of 40 HST. The highest average value was found in the treatment of 4 g Humic Acid administration and 8 ml Nasa POC concentration showing a higher average value compared to other treatments.